The Effect of Financial Decisions on the Value of Banking Companies Listed on the Indonesia Stock Exchange, 2018-2020 - Wiritanaya, Igga Mellianda; Aminah, Siti (Faculty of Economics and Business UNTAG Semarang, 2022)
This study aims to determine the effect of investment decisions, funding decisions, and dividend policy on firm value in banking companies listed on the Indonesia Stock Exchange in 2018-2020. This research is classified as a quantitative approach. The sample in this study was 12 banking companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 periods. Sampling used the census technique. The data analysis technique used multiple linear regressions. The results of the study show that investment decisions have a positive and significant effect on firm value. Funding decisions have a negative and insignificant effect on firm value. Dividend policy has a positive and significant effect on value. Investment decisions, funding decisions and dividend policies affect the value of banking companies listed on the Indonesia Stock Exchange.